Safeguarding Women’s Rights in Divorce in Absentia: The Role of Ex Officio Judicial Powers in Iddah Maintenance - Rita Latassaqia; Sukron Ma'mun; Fitrat Umirov (Al-Syakhsiyyah: Journal of Law and Family Studies, 2026)
This study is motivated by the increasing number of divorce cases involving the absence of the wife, which raises significant concerns regarding the protection of women’s rights, particularly in relation to the fulfillment of iddah maintenance. In judicial practice, such absence frequently results in the non-fulfillment of these rights, thus necessitating legal innovation. This research examines the exercise of ex officio judicial authority to impose iddah maintenance in cases involving an absent wife, analyzed from the perspective of maṣlaḥah. Adopting a descriptive qualitative approach, the study analyses Decision No. 5573/Pdt.G/2023/PA.Sbr, which illustrates the court’s proactive role in safeguarding the wife’s rights notwithstanding her absence from the proceedings. This approach is consistent with the principle of maṣlaḥah, particularly in prioritizing primary necessities (ḍarūriyyāt). The findings indicate that ex officio authority is a vital instrument for addressing gaps in formal law and realizing substantive justice. In practice, this research provides a normative basis for standardizing the application of ex officio authority in default cases, with a view to reducing the neglect of women’s financial rights. It further offers strategic recommendations for the Supreme Court to develop technical guidelines requiring consideration of the wife’s rights in all divorce decisions involving absent parties. By institutionalizing progressive judicial reasoning, this study contributes to strengthening a system of religious justice that is responsive to women’s rights and oriented towards the public welfare.